The Reality of Internal Marketing in the Iraqi Banks: An Analytical Study in the Middle East Bank for Investment and Finance - Abdullah Mahmood Abdullah; Marwan Rashid Hammood; Yassir Maolod Hajem (Research Parks Publishers, 2023)
The study aims at investigating the reality of internal marketing dimensions in the Middle East Bank for Investment and Finance. The descriptive analytical approach is employed in this study. The data is collected through using the questionnaire as a main tool of the study. The research community is represented by (55) individuals. A non-random sampling is selected using census method due to the small size of community. The results are analyzed using the (SMART, PLS4) program to test the hypotheses under study. It is found that the dimensions of internal marketing in the Middle East Bank represent the objectives of the bank and that they are available and characterized by trustworthiness and reliability. In addition, these dimensions vary in terms of their importance in the bank under study according to their performance. The sequence of dimensions starts from the selection of employees, followed by empowerment, then internal communications, after that training, and finally motivation. This study is important for the literature on marketing management by highlighting the importance of internal marketing dimensions in the banking sector in developing countries, particularly Iraq.